2013
DOI: 10.1042/bj20130085
|View full text |Cite
|
Sign up to set email alerts
|

Membrane topology of yeast alkaline ceramidase YPC1

Abstract: Condensed title: Topology of yeast alkaline ceramidase YPC1Key words: YPC1, ceramidase, topology, cysteine accessibility, CREST superfamily Abbreviations: DHS, dihydrosphingosine; DTR, dual topology reporter; DTT, dithiothreitol; FOA, 5'-fluoroorotic acid; IPC, inositolphosphorylceramide; LCB, long chain base; MIPC, mannosyl-IPC; M(IP) 2 C, inositolphosphoryl-MIPC; NEM, N-ethylmaleimide; PEG-mal, PEG-5000-maleimide; PHS, phytosphingosine; RT, room temperature; SCAM TM , substituted cysteine accessibility metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, Ypc1p may reside in membrane domains enriched in C24:0 and C26:0. Ypc1p has its active site on the luminal side of the ER (Ramachandra & Conzelmann, ), and the concentrations of various fatty acids in the luminal leaflet of the ER are presently not known. We could not detect IPCs with a C16:0 as fatty acid after growing 2∆.YPC1 cells in medium containing C16:0 (not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Ypc1p may reside in membrane domains enriched in C24:0 and C26:0. Ypc1p has its active site on the luminal side of the ER (Ramachandra & Conzelmann, ), and the concentrations of various fatty acids in the luminal leaflet of the ER are presently not known. We could not detect IPCs with a C16:0 as fatty acid after growing 2∆.YPC1 cells in medium containing C16:0 (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even when expressed from their endogenous promoters, they may contribute to ceramide biosynthesis if Lac1p and Lac1p are not operational. Moreover, the reverse ceramidase activity of Ypc1p and Ydc1p in microsomal detergent extracts from wild-type (WT) cells can easily be detected and is quite substantial, as expression of GAL1 promoter driven YPC1, placed on a 2 l or a centromeric vector, increases the activity only 25 and 2.3-fold over WT levels, respectively (Mao et al, 2000a;Ramachandra & Conzelmann, 2013; therein Supporting Information, Fig. S2d).…”
Section: Physiological Expression Levels Of Ypc1p and Ydc1pmentioning
confidence: 99%
“…Materials were from sources described recently ( Ramachandra and Conzelmann, 2013 ). [ 3 H] myo -inositol and [ 14 C]serine were from ARC Radiochemicals (St. Louis, MO); rhodamine phalloidin and Prolong Gold antifade reagent were from Invitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…To exclude the possibility that Ypc1p protein per se may affect the expression of other LCB metabolic enzymes, a catalytically inactive mutant of this enzyme was constructed as a negative control by site-directed mutagenesis as described in the experimental procedure. We mutated Ypc1p by replacing Cys 27 with Phe to generate the Cys 27 > Phe 27 mutant, named Ypc1p-C27F because it was reported that Cys 27 is essential for Ypc1p's reverse activity [24]. We generated a yeast stain that overexpresses Ypc1p or Ypc1p-C27F under the control of a Gal1 promoter.…”
Section: Resultsmentioning
confidence: 99%
“…To exclude the possibility that Ypc1p per se may induce biological effects independently of its lipid mediator, a catalytically inactive mutant of this enzyme was constructed as a negative control. Ypc1p was mutated by replacing Cys 27 with Phe to generate the Cys 27 > Phe 27 mutant [24], named Ypc1p-C27F, by a QuikChange II XL Site-Directed Mutagenesis Kit (Agilent Technology, CT) following the manufacturer's manual. The ORF of Ypc1p-C27F was cloned into a pYES2 vector, and the resulting expression construct, pYES2::YPC1 C27F , was transformed into yeast cells as described previously.…”
Section: Methodsmentioning
confidence: 99%